Controlling Between Autonomy and Heteronomy - Todorović – Dudić, Aleksandra (International Journal of Industrial Engineering and Management, 2015)
The strategic playing field of controllers from the perspective of the services to be delivered and the relationships to internal customer, were frequent references to how controllers should adapt their abilities to such challenges. Controllers should therefore under no circumstances take comfort in their very strong internal competitive position, but have to work actively on its ongoing strategic development. If controllers focus consistently on identifying new services for managers, if they keep their managers' satisfaction in mind, if they measure their tasks in the same way that they plan and monitor business development, then there are strong arguments why they should be able to maintain their „market dominance“ in the area of management support. Article history: Received (26.10.2015); Revised (05.12.2015); Accepted (13.12.2015)